Study of Creative Thinking Ability in Project Learning through Field Trip at Lake Tangkas Jambi - Budiarti, Retni Sulistiyoning; Harlis, Harlis (JIPVA (Jurnal Pendidikan IPA Veteran); Vol 7 No 2 (2023): JIPVA (Jurnal Pendidikan IPA Veteran), 2023)
Natural learning resources that highlight the local wealth of the region are a good means to facilitate student creativity, and one such resource is Lake  Tangkas. The aim of this research is to analyze students' creative thinking abilities and identify the strengths and weaknesses of field trips to Danau Tangkas. This study is a descriptive exploratory research enriched by in-depth interviews. Data analysis is conducted quantitatively and qualitatively. The results of the research show that the criteria for very creative thinking ability are 19%, creative thinking 38%, not creative 29%, and very uncreative 14%. Furthermore, 90% of students chose ideas related to plants, while only 10% chose ideas related to animals in the Danau Tangkas area. The percentage of creative thinking indicators is as follows: novelty 75%, flexibility 55%, and proficiency 65%. In conclusion, the research indicates the potential to develop students' creative thinking abilities and emphasizes the importance of focusing on ideas related to plants in projects at Lake Tangkas, Jambi.